Pendidikan Pancasila Sebagai Kerangka Etika Dalam Penggunaan Kecerdasan Buatan - Nathaniel Steave Harjanto; Fatma Ulfatun Najicha (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
Pancasila is the philosophical basis of the Indonesian state which has deep ethical values. In the context of artificial intelligence (AI) innovation, Pancasila education can act as an important ethical framework. This article discusses how Pancasila education can be used as an ethical foundation in the development and implementation of AI. The discussion includes understanding the values of Pancasila, how these values can be applied in AI, and the positive impacts that can be produced in terms of ethics, morals and social matters. Apart from that, this article also highlights the challenges that may arise in integrating Pancasila values ​​into AI and the solutions that can be taken to overcome these challenges. The result of using Pancasila as an ethical framework in artificial intelligence innovation is to create AI that is more humane, fair, and has a positive impact on Indonesian society and the world in general. This article provides a comprehensive view of the role of Pancasila education in steering AI in a more ethical and beneficial direction.